Critical Geography in Preschool: Evidence of Early Childhood Civic Action and Ideas about Justice. Issue 7 (July 2020) - Payne, Katherina A.; Falkner, Anna; Adair, Jennifer Keys
Background: U.S. preschool children from Latinx immigrant and Black communities often experience schooling rooted in compliance and overdiscipline. In these contexts, schools do not recognize the rich lived experiences of Children of Color as suitable for civic learning. This article explores how, when schools value young Children of Color as capable and their work as important, classrooms become sites of children's daily embodied civic action. Purpose: Our study sought to better understand how children conceptualize and enact their ideas about community and to document the kinds of civic action present in early childhood classrooms. Applying theoretical tools of critical geography, we specifically analyzed how children used space and materials to enact their vision of a just community. Participants: Three classrooms—an inclusion classroom, a bilingual classroom, and an English-only general education classroom—located within a Head Start center in South Texas participated in this study. The campus is roughly 65% Latinx, 33% Black, and 2% White, serving 3-, 4-, and 5-year-old children. Research Design: This study used a multisited, comparative ethnographic methodology. Multisited ethnography allows researchers to locate patterns and contextual differences that impact people's lived experiences. Initially, researchers conducted ethnographic observations through field notes, photographs, and short videos documenting children's action on behalf of or with the classroom community. Next, we used video-cued ethnographic methods, filming for three days in each classroom and editing the footage into a 20-minute film. We showed that film to teachers, families, and children in focus groups. Analysis occurred in multiple phases, during which we refined codes through individual, partner, participant, and team-level work. Findings: Children used physical space and materials to assert community membership and to strengthen community ties. They adapted space and classroom materials to include other community members in shared activities. Finally, children advocated for space for their own purposes. Conclusions: When teachers and administrators approach the classroom as a civic space where children representing racial, linguistic, and ability diversity can access embodied experiences with civic action, children can use their space to act on behalf of the community. Rather than offering lesson-based social-emotional learning, schools can reflect on how children might build a just, caring community through authentic embodied experiences that include having some control over space and materials. Doing so may allow a shift toward class environments that support shared endeavors and opportunities for children to care for community members.